2012
DOI: 10.1007/s10103-012-1170-8
|View full text |Cite
|
Sign up to set email alerts
|

Reliability evaluation of alumina-blasted/acid-etched versus laser-sintered dental implants

Abstract: Step-stress accelerated life testing (SSALT) and fractographic analysis were performed to evaluate the reliability and failure modes of dental implant fabricated by machining (surface treated with alumina blasting/acid etching) or laser sintering for anterior single-unit replacements. Forty-two dental implants (3.75×10 mm) were divided in two groups (n021 each): laser sintered (LS) and alumina blasting/acid etching (AB/AE). The abutments were screwed to the implants and standardized maxillary central incisor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…The lack of long-term studies reporting on prosthetic survival rates on narrow implants has recently been pointed out [27], which indicates the need of clinical trials that supports previous in vitro evaluation of their performance considering that an important failure mechanism in metals is fatigue [31]. The step-stress accelerated life testing method utilized in the present study consists in testing the samples at higher stress levels in order to accelerate failures, although every sample is subjected to progressively increasing loads which start at low levels before reaching the above mentioned higher levels [21,30,[32][33][34][35]. These failures are distributed over three different profiles allowing statistical predictions for a given load and cycle mission.…”
Section: Discussionsupporting
confidence: 69%
“…The lack of long-term studies reporting on prosthetic survival rates on narrow implants has recently been pointed out [27], which indicates the need of clinical trials that supports previous in vitro evaluation of their performance considering that an important failure mechanism in metals is fatigue [31]. The step-stress accelerated life testing method utilized in the present study consists in testing the samples at higher stress levels in order to accelerate failures, although every sample is subjected to progressively increasing loads which start at low levels before reaching the above mentioned higher levels [21,30,[32][33][34][35]. These failures are distributed over three different profiles allowing statistical predictions for a given load and cycle mission.…”
Section: Discussionsupporting
confidence: 69%
“…The authors concluded that the normalized endurance limits of the tested structures were lower than that of solid titanium (with similar alloy) and that of some other porous titanium structures manufactured using other techniques [ 54 ]. Almeida and colleagues [ 55 ] investigated the mechanical behaviour of DMLS titanium dental implants. Step-stress accelerated life testing (SSALT) and fractographic analysis were performed to compare the reliability and failure modes of DMLS and sandblasted-acid etched (SAE) implants used for anterior single-unit replacements [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Almeida and colleagues [ 55 ] investigated the mechanical behaviour of DMLS titanium dental implants. Step-stress accelerated life testing (SSALT) and fractographic analysis were performed to compare the reliability and failure modes of DMLS and sandblasted-acid etched (SAE) implants used for anterior single-unit replacements [ 55 ]. Forty-two standard dental implants (3.75 mm × 10.0 mm) were used; among these implants, 21 were fabricated with DMLS technology while the other 21 were SAE implants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation